2013
DOI: 10.1371/journal.pone.0052968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensory Behavioral Tasks on Pain Threshold and Cortical Excitability

Abstract: Background/ObjectiveTranscutaneous electrical stimulation has been proven to modulate nervous system activity, leading to changes in pain perception, via the peripheral sensory system, in a bottom up approach. We tested whether different sensory behavioral tasks induce significant effects in pain processing and whether these changes correlate with cortical plasticity.Methodology/Principal FindingsThis randomized parallel designed experiment included forty healthy right-handed males. Three different somatosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…This finding corroborates the study of Volz et al (2013), which reported 70% reduction of chronic and acute pain after vibration therapy. They concluded that vibration stimulus increases neuronal conduction of signals, through the large diameter myelinated fibers, and inhibits short fibers of spinal dorsal horn before the synapse.…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates the study of Volz et al (2013), which reported 70% reduction of chronic and acute pain after vibration therapy. They concluded that vibration stimulus increases neuronal conduction of signals, through the large diameter myelinated fibers, and inhibits short fibers of spinal dorsal horn before the synapse.…”
Section: Discussionsupporting
confidence: 92%
“…Because chronic pain patients have a deficient pain matrix and altered pain-related neural networks, such methods as mental imagery might induce differential effects in patients versus healthy subjects [ 8 , 16 , 25 , 26 ]. In previous studies, we found that motor tasks, sensory stimuli, and movement observation can change pressure pain threshold levels and cortical excitability [ 10 , 27 , 28 ] (Figure 1 c), in which active tasks for one hand can ameliorate the perception of pain in the targeted hand. In contrast, we also found that the untargeted hand experienced a decrease in pain threshold, indicating greater perception of pain [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 87%
“…In previous studies, we found that motor tasks, sensory stimuli, and movement observation can change pressure pain threshold levels and cortical excitability [ 10 , 27 , 28 ] (Figure 1 c), in which active tasks for one hand can ameliorate the perception of pain in the targeted hand. In contrast, we also found that the untargeted hand experienced a decrease in pain threshold, indicating greater perception of pain [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 87%
“…Proprioceptive impairments might be mediated by disruption of mechanoreceptors in the diseased joint structures or changes in muscle receptors (e.g., muscle spindles) secondary to muscle changes associated with OA (Felson, 2004;Knoop et al, 2011). There could also be interference with relay of proprioceptive information in the spinal cord secondary to nociceptive input (Chalmers, 2004;Hultborn, 2001;Volz et al, 2013). Changes in processing of somatosensory information at higher centers such as the cortex have also been implicated.…”
Section: Introductionmentioning
confidence: 99%